Characterizing metastatic uveal melanoma patients who develop symptomatic brain metastases - Wei, Alexander Z.; Uriel, Matan; Porcu, Agata; Manos, Michael P.; Mercurio, Ann C.; Caplan, Michael M.; Hulse, Liam; Seedor, Rino S.; Holovatska, Marta; Francis, Jasmine; Khan, Shaheer A.; McDonnell, Diana E.; et al. (Frontiers in Oncology, 2022)
Metastatic uveal melanoma (mUM) is an advanced ocular malignancy characterized by a hepatotropic pattern of spread. As the incidence of brain metastases (BM) in mUM patients has been thought to be low, routine CNS surveillance has not been recommended. Notably, no formal assessment of BM incidence in mUM has to date been published to support this clinical practice. We aimed to determine the true rate of BM in mUM and to clarify the clinical and genomic risk factors associated with BM patients through a collaborative multicenter, retrospective research effort. Data collected from 1,845 mUM patients in databases across four NCI-designated comprehensive cancer centers from 2006-2021 were retrospectively analyzed to identify patients with BM. Brain imaging in most cases were performed due to onset of neurological symptoms and not for routine surveillance. An analysis of demographics, therapies, gene expression profile, tumor next generation sequencing (NGS) data, time to metastasis (brain or other), and survival in the BM cohort was completed. 116 out of 1,845 (6.3%) mUM patients were identified with BM. The median age at time of UM diagnosis was 54 years old (range: 18-77). The median time to any metastasis was 4.2 years (range: 0-30.8). The most common initial metastatic site was the liver (75.9%). 15/116 (12.9%) BM patients presented with BM at the time of initial metastatic diagnosis. Median survival after a diagnosis of BM was 7.6 months (range: 0.4-73.9). The median number of organs involved at time of BM diagnosis was 3 (range: 1-9). DecisionDX-UM profiling was completed on 13 patients: 10-Class 2, 2-Class 1B, and 1-Class 1A. NGS and cytogenetic data were available for 34 and 21 patients, respectively. BM was identified in 6.3% of mUM cases and was associated with high disease burden and a median survival of under 8 months once diagnosed. Since most patients in this cohort were symptomatic, the incidence of asymptomatic BM remains unknown. These data suggest the use of routine brain imaging in all mUM patients at risk for developing BM for early detection.